Delivery of livestock healthcare services and scope for its improvement: Evidence from Uttar Pradesh, India - BARDHAN, D; KUMAR, SANJAY; SINGH, RISHI KUMAR (The Indian Journal of Animal Sciences, 2018)
The study ascertained the use pattern of animal healthcare services (AHS) by the livestock farmers and to assess the impact of potential reforms in animal health delivery system (AHDS) in Uttar Pradesh, the largest state in India. A total of 1,037 households from all the 9 agro-climatic regions of the state were surveyed. Households were categorized in to poor (48%), medium (36.5%) and rich (15%) wealth categories to assess equity implications of potential reforms in AHDS. Analysis of use pattern of AHS revealed that quacks were the predominant AHS providers, followed by para-veterinarians and government veterinary officers (GVO’s). Out of the total sample visits made by GVO’s and para-vets, 58% and 66%, respectively, were attended at-home. The number of at-home visits by GVO’s per household increased with increase in wealth status. Richer households paid significantly higher prices per visit to AHS providers as compared to poor households. Even then, the average price paid by the poor households were substantially high. Contingent valuation method used to elicit farmers’ willingness to pay for animal healthcare services revealed that the amount they are willing to pay increased with increase in wealth status. Analysis of factors influencing farmers’ WTP revealed that lower wealth status and distance to market negatively influences the farmers’ likelihood of willing to pay a higher amount. On the other hand, household head education, easy credit availability and scale of milk production positively influenced the probability that a farmer will be willing to pay a higher amount.